Materiology : the creative's guide to materials and technologies. - Kula, Daniel, ....-; Ternaux, Elodie, ....- (Amsterdam : Frame, 2009)
A book intended for all creative professionals who rely on materials and technologies ? architects, designers, stylists, artists and the like, from students to experienced practitioners ? Materiology is written in a style that conveys a wealth of information in a language that?s easy to understand. This book covers everything you always wanted to know about materials and technologies but never expected to find in a single volume. Materiology?s comprehensive exploration of materials is divided into four sections: 1. Categories of materials: various types of wood, plastic, glass, metal, lighting, etc.- 2. Catalogue of materials: 150 catalogue cards that identify various materials, from the most basic substance to the latest cutting-edge innovation.- 3. Processes: major methods of processing materials (e.g. injection moulding, extrusion) explained with instructive diagrams.- 4. Thinking out of the box: issues of relevance to any study of materials and technologies, everything from ecology to virtual issues.